Development and In-Vitro Evaluation of Betahistine Hydrochloride microspheres by Emulsification Solvent Evaporation Method - Wathore, Sandeep A (Asian Journal of Pharmaceutical Research and Development, 2019)
The formulation of floating microspheres of Betahistine hydrochloride by the o/w emulsification and solvent evaporation method in the presence of tween 80 as an emulsifying agent. The influence of formulation factor Drug: Polymer ratio on particle size, encapsulation efficiency and invitro release characteristics of the microspheres were investigated. The microspheres have been analyzed for their size, drug loading capacity and drug release study. Spherical and smooth surfaced microspheres with desired encapsulation efficiencies were obtained. Slow drug release from microspheres observed up to 12 h. for formulation F4, F5. Optimized formulation F4 was evaluated for FTIR, DSC, SEM. DSC and FTIR studies showed that the nature of pure drug Betahistine hydrochloride remains unaffected till the completion of process of microspheres formation. SEM photographs showed that the Floating microspheres were spherical in nature with smooth surface and uniform distribution of the drug within the microsphere. Keywords: